Implementing Independence-Oriented Character Education at Al-Mujahidin Integrated Islamic Boarding School, Balikpapan - Mukhoyyaroh, Nurul Badi’; Yusuf, Iskandar (Journal of Educational Research and Practice, 2024)
This research aims to determine the implementation of independence character education at the Al-Mujahidin Balikpapan Integrated Islamic Boarding School, in order to find strategies for instilling independent character values in students. This research is a descriptive qualitative research method with a focus interview approach. The data collection techniques used in this research are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of this research show that the strategy for cultivating the character of independence has been implemented at the beginning of entering santri at the Islamic boarding school, but in line with the cultivation of independence character education, of course there are challenges and obstacles in the process of fostering independence for students.